SEESAW MEDIA: DIGITAL NATIVES’ PREFERENCE IN 4.0 SPEAKING LEARNING CLASS - Muhammad Rauuf Oktavian Nur; Ikrar Genidal Riadil (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
Digital Natives students born into an era of instant networking. It makes everything have a connection with technologies. Digital natives having sophisticated technology knowledge and skills that can be potentially harnessed for better learning engagement inside the classroom. Seesaw is a simple way for teachers and students to record and share what's happening in the speaking classroom. Seesaw gives students a place to document their learning, be creative and learn how to use technology in language learning class. This paper will discuss the seesaw application within implementation problems and its solutions. The researcher will use a qualitative study for this research. The study's data is collected from the second semester until sixth-semester students of English Department at Tidar University. The conclusion, in this paper, is seesaw application fits with this generation of learners because it allows them to communicate with their instructors in real-time from the first day of class.SEESAW MEDIA: DIGITAL NATIVES’ PREFERENCE IN 4.0 SPEAKING LEARNING CLASS